1996
DOI: 10.1016/0014-5793(96)00808-3
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor α (TNFα) induces pro‐matrix metalloproteinase 9 production in human uterine cervical fibroblasts but interleukin 1 α antagonizes the inductive effect of TNFα

Abstract: We have examined the regulation of precursor of matrix metalloproteinase 9 (proMMP-9)lprogelatinase B production by tumor necrosis factor et (TNFet) and interleukin let (H-let) using human uterine cervical fibroblasts. TNF~ but not IL-la, induces the production of proMMP-9 in the cervical cells. IL--let, however, suppresses the TNFet-ioduced proMMP-9 production. 12-O-tetradeeanoylphorbol 13-acetate (TPA) also stimulates the cervical cells to produce proMMP-9, and IL-let synergistically enhances its production.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…Gelatin Zymography-Gelatinolytic activity in the harvested culture media was detected by gelatin zymography with 10% (w/v) acrylamide gel containing gelatin (0.6 mg/ml; Difco) as described previously (37).…”
Section: Methodsmentioning
confidence: 99%
“…Gelatin Zymography-Gelatinolytic activity in the harvested culture media was detected by gelatin zymography with 10% (w/v) acrylamide gel containing gelatin (0.6 mg/ml; Difco) as described previously (37).…”
Section: Methodsmentioning
confidence: 99%
“…41 Some mesenchymal cells also produce this enzyme in response to certain stimuli. [42][43][44] Our coimmunolocalization studies of MMP-9 and HAM-56 in AAA aortic tissue showed that MMP-9 is a product of macrophages. Although these results are consistent with those of in situ hybridization studies by Thompson et al 21 and McMillan et al, 23 Patel et al 34 reported that AAA-derived SMCs in culture produce MMP-9.…”
mentioning
confidence: 86%
“…For immunoblotting, proteins of the culture medium (10 µl from 1×10 6 cells) separated by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) under reducing conditions were transferred onto a nitrocellulose membrane. The membrane was blocked and treated for 1 h at room temperature with antibodies against human MMPs (anti-humanproMMP-1, proMMP-2, proMMP-3 and proMMP-9) [10,15]. The rest of the samples were stored at -80°for further Western blotting as controls.…”
Section: Western Blot Analysismentioning
confidence: 99%